Resiliensi Psikospiritual pada Mahasiswa Broken Home (Psychospiritual Resilience among Students from Broken Homes) - Yani Husain At Thohari, Muhammad; Balgies, Soffy (Happiness: Journal of Psychology and Islamic Science, 2025)
This study aims to explore the dynamics of psychospiritual resilience among students from broken-home families in the Department of Sufism and Psychotherapy at UIN Sunan Ampel Surabaya. The study is motivated by the increasing psychological challenges experienced by students from disrupted family backgrounds and the growing recognition of spirituality as a resource for resilience. A qualitative approach with phenomenological design was employed. Ten participants were selected through purposive sampling based on two criteria: being active students in the Department of Sufism and Psychotherapy and having a broken-home family background. Data was collected through in-depth interviews, participant observation, and documentation, and was analyzed using thematic analysis. The findings revealed four major themes underlying psychospiritual resilience: (1) spirituality as a means of emotional regulation through practices such as dhikr, prayer, Qur’anic recitation, and self-reflection; (2) meaning-making of broken-home experiences as a process of personal growth and life learning; (3) social support from peers, academic environments, and religious communities as a reinforcing factor of resilience; and (4) psychospiritual transformation characterized by increased optimism, independence, and positive future orientation. The findings indicate that psychospiritual resilience is formed through a dynamic interaction among psychological, spiritual, and social dimensions. Theoretically, this study contributes by integrating the concept of Tazkiyah al-Nafs with Antonovsky’s Salutogenesis Theory to form a comprehensive framework for understanding psychospiritual resilience among students from broken-home families.